A MOTAD Approach to Risk Management Strategies for Vegetable Producers in Malaysia - Mohamed, Zainal Abidin; Baharumshah, Ahmad Zubaidi (1991)
Most farm decisions are made under conditions of risk and uncertainty. In the last two decades, researchers in the agricultural economics discipline have increased their research efforts in finding convenient methods of incorporatingrisk directly in farm decision making models. MOTAD (Minimization of Total Absolute Deviation) developed by Hazell is an important result of these efforts and it has become a common method of incorporating risk in farm analysis. In this paper the MOTAD model is discussed and an empirical example is provided to show how the model can be used by managers to improve farm plans.